From Knowledge To Money – An Industrial Perspective Of Knowledge Management - Annamalai, V.E. (Journal of Knowledge Management Practice, 2010)
Any manufacturing business runs on specific procedures that need to be repeated consistently and improved upon continuously. While already known procedures are laid down as ISO documents, each individual learns his own way of doing things, within the framework of the defined procedures. Such learnings happen everyday in shopfloor to various persons under various situations. Only those firms which can constantly capture such intrinsic knowledge that happens every day in the shopfloor, can be competitive and sustainable. The present case study describes methods followed by an Organization to capture these intrinsic learnings of the workforce and to put them to effective use for business gain on a regular basis. Based on the study, a model for identification of expertise and method of delayering the same is also developed.